2021
DOI: 10.1109/access.2021.3096776
|View full text |Cite
|
Sign up to set email alerts
|

Person Identification From Audio Aesthetic

Abstract: Behavioral biometrics survey actions rather than the physical traits of the person. Within this categorization, social behavioral biometrics utilizes an individual's communications for biometric analysis. The investigation of the uniqueness of human preferences and their implications to other aspects of an individual, such as personality or gender, is both a psychological and a biometric problem. An emerging approach is the usage of an individual's aesthetic preferences for the purpose of person identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The user count in FMA dataset is 34, while for MPD dataset it is 200. The audio aesthetic system introduced by Sieu and Gavrilova [5] achieved a rank 1 accuracy of 95.74% on the FMA dataset and 99.70% accuracy on the MPD dataset. Furthermore, in their work, the inference time for FMA and MPD datasets was 1.85s and 8.12s, respectively.…”
Section: E Performance Comparison With State-of-the Art Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The user count in FMA dataset is 34, while for MPD dataset it is 200. The audio aesthetic system introduced by Sieu and Gavrilova [5] achieved a rank 1 accuracy of 95.74% on the FMA dataset and 99.70% accuracy on the MPD dataset. Furthermore, in their work, the inference time for FMA and MPD datasets was 1.85s and 8.12s, respectively.…”
Section: E Performance Comparison With State-of-the Art Resultsmentioning
confidence: 98%
“…The very first audio aesthetic system was developed in 2021 and achieved a significant accuracy by extracting handcrafted audio features from user liked-songs [5]. This research demonstrated that, similar to visual aesthetics, audio aesthetic features have unique and distinguishing characteristics for biometric identification.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations